EVENT-DRIVEN MICROSERVICES FOR SYNCHRONIZATION FIDELITY IN HOSPITAL DIGITAL TWIN SYSTEMS - KRISHNA MATTAM (IPHO-Journal of Advance Research in Science And Engineering, 2026)
INTRODUCTION: Hospital operations face critical inefficiencies in emergency department flow, ICU capacity planning, and patient admissions management. Legacy monolithic IT architectures are fundamentally ill-equipped to support the high-frequency, real-time data synchronization that operationally actionable digital twins require. OBJECTIVES: This article investigates how event-driven architectures (EDA) and cloud-native microservices enable the synchronization fidelity necessary to deploy hospital digital twins as dynamic, real-time operational tools rather than static descriptive simulations. METHODS: A structured narrative synthesis of peer-reviewed literature was conducted, drawing from PubMed, IEEE Xplore, Scopus, and the ACM Digital Library, using a systematic search protocol with defined inclusion and exclusion criteria, reported in accordance with the PRISMA framework. RESULTS: Microservices provide essential architectural modularity by decomposing monolithic systems into independently scalable services. EDA, via asynchronous event streaming through platforms such as Apache Kafka and Azure Event Grid, acts as the definitive enabling layer coupling physical hospital environments with their digital replicas. Key findings confirm latency reductions enabling real-time predictive simulation across trauma, triage, and capacity planning contexts. Significant tensions between scalability and data privacy, alongside interoperability barriers, remain unresolved. CONCLUSION: A tri-layer conceptual framework — comprising the physical context layer, the event-driven microservices layer, and the agent-based digital twin layer — is proposed to guide future hospital digital twin deployments and inform both IT governance and security policy.